LASER ABLATION OF PAINT COATINGS IN INDUSTRY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
A comparison is made between the laser and sandblasting methods for removing paint from industrial facilities. The advantages of laser ablation are discussed. The possibilities of laser paint removal systems - stationary and moving - are shown. The main factors influencing the laser ablation process and the indicators that determine the quality of the obtained surface are systematized. Researchers' publications on this technological process are analyzed.